Introducing the Discriminative Paraconsistent Machine (DPM) - Guido, Rodrigo Capobianco [UNESP]; Barbon Junior, Sylvio; Solgon, Regiane Denise; Paulo, Kátia Cristina Silva; Rodrigues, Luciene Cavalcanti; Silva, Ivan Nunes da; Escola, João Paulo Lemos (My University, 2013)
This paper introduces a new tool for pattern recognition. Called the Discriminative Paraconsistent Machine (DPM), it is based on a supervised discriminative model training that incorporates paraconsistency criteria and allows an intelligent treatment of contradictions and uncertainties. DPMs can be applied to solve problems in many fields of science, using the tests and discussions presented here, which demonstrate their efficacy and usefulness. Major difficulties and challenges that were overcome consisted basically in establishing the proper model with which to represent the concept of paraconsistency.
Keywords: Paraconsistency; Pattern recognition; Discriminative model training